2021
DOI: 10.5194/we-21-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Frog vocalization is influenced by moon phases: Brazilian frogs tend to prefer low-albedo phases

Abstract: Abstract. Lunar phases remarkably influence the circadian cycle of living beings. Early amphibian studies date back to the 1960s, but only recently has more research been conducted in this field. Much still needs to be understood to establish the behavioral pattern of this group according to the synodic cycle. In the present study, we sought to determine (i) whether the vocalization activity was influenced by the lunar phases and (ii) whether the influence was species-specific or affects the community with equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The lunar cycle may have a balanced coverage in terrestrial studies as its influence is established for seabirds (Mougeot and Bretagnolle 2000), but it could also have been randomly evenly sampled. Nonetheless, the cycle should be explicitly considered for more taxa, especially for nocturnal or crepuscular ones which exhibit behavioral plasticity depending on lunar illumination (Kronfeld-Schor et al 2013;Appel et al 2017;Lima et al 2021;Ferreira et al 2020;Schaaf, Boullhesen, and Akmentins 2023). Climate and land use change will impact soundscapes in unpredictable ways through changing species distributions and phenology, thereby justifying the need for better coverage across multiple time scales -including inter-annual ones -to monitor changes in the ecosystems (Desjonquères et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The lunar cycle may have a balanced coverage in terrestrial studies as its influence is established for seabirds (Mougeot and Bretagnolle 2000), but it could also have been randomly evenly sampled. Nonetheless, the cycle should be explicitly considered for more taxa, especially for nocturnal or crepuscular ones which exhibit behavioral plasticity depending on lunar illumination (Kronfeld-Schor et al 2013;Appel et al 2017;Lima et al 2021;Ferreira et al 2020;Schaaf, Boullhesen, and Akmentins 2023). Climate and land use change will impact soundscapes in unpredictable ways through changing species distributions and phenology, thereby justifying the need for better coverage across multiple time scales -including inter-annual ones -to monitor changes in the ecosystems (Desjonquères et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moonlight affects time partitioning of activity in amphibians (Vignoli et al, 2014;Onorati and Vignoli, 2017;Bissattini, Buono and Vignoli, 2020). Several studies reported more reproduction events (Vignoli and Luiselli, 2013;Onorati and Vignoli, 2017), more intense calling activity (Lima et al, 2021), increased mobility (FitzGerald and Bider, 1974;Henrique and Grant, 2019), or higher general activity (Muller, Cade and Schwarzkopf, 2018) at lower moonlight intensities. However, the effect of moonlight on amphibian activity is conflicting, with an even number of studies where activity increased or decreased during full moon, suggesting that the response depend on the species (Grant, Halliday and Chadwick, 2013).…”
Section: Introductionmentioning
confidence: 99%